Plasma membrane phospholipase A2 controls hepatocellular fatty acid uptake and is responsive to pharmacological modulation: implications for nonalcoholic steatohepatitis. Issue 7 (9th April 2014) - Stremmel, Wolfgang; Staffer, Simone; Wannhoff, Andreas; Pathil, Anita; Chamulitrat, Walee
ABSTRACT: Excess hepatic fat accumulation leads to nonalcoholic steatohepatitis (NASH), a serious threat to health for which no effective treatment is available. However, the mechanism responsible for fatty acid uptake by hepatocytes remains unclear. Using the human hepatocyte‐derived tumor cell line HepG2, we found that fatty acid influx is mediated by a heterotetrameric plasma membrane protein complex consisting of plasma membrane fatty acid‐binding protein, caveolin‐1, CD36, and calcium‐independent membrane phospholipase A2 (iPLA2 β). Blocking iPLA2 β with the bile acid‐phospholipid conjugate ursodeoxycholate‐lysophosphatidylethanolamide (UDCA‐LPE) caused the dissociation of the complex, thereby inhibiting fatty acid influx (IC50 47 μM), and suppressed the synthesis of all subunits through a reduction in lysophosphatidylcholine from 8.0 to 3.5 μmol/mg of protein and corresponding depletion of phosphorylated c‐Jun N‐terminal kinase. These findings were substantiated by an observed 56.5% decrease in fatty acid influx in isolated hepatocytes derived from iPLA2 β‐knockout mice. Moreover, steatosis and inflammation were abrogated by UDCA‐LPE treatment in a cellular model of NASH. Thus, iPLA2 β acts as an upstream checkpoint for mechanisms that regulate fatty acid uptake, and its inhibition by UDCA‐LPE qualifies this nontoxic compound as a therapeutic candidate for the treatment of NASH.—Stremmel, W., Staffer, S., Wannhoff, A., Pathil, A., Chamulitrat, W. Plasma membrane phospholipase A2 controls hepatocellular fatty acid uptake and is responsive to pharmacological modulation: implications for nonalcoholic steatohepatitis. FASEB J . 28, 3159–3170 (2014). www.fasebj.org